(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article touches on the problem as formation of scholars’ vocal speech experience, that demands efficacious solution in definite didactic condition. Among of such conditions the author emphasizes the major: students’ acquisition of knowledge, skills and experience of vocal culture’s foundation; application of intonation phonopathy exercises by V.V. Yerne Ivanov methodics; systematic, gradual and purposeful work information of scholars’ vocal speech experience.